Structural diversity in a series of metal-organic frameworks (MOFs) composed of divalent transition metals, 4,4 `-bipyridine and a flexible carboxylic acid - Pachfule, Pradip; Panda, Tamas; Dey, Chandan; Banerjee, Rahul (Crystengcomm, 2010)
A series of flexible metal-organic frameworks (MOFs) have been successfully synthesized under hydrothermal condition using 1,3-adamantanediacetic acid (C(14)H(20)O(4), H(2)ADA) as a flexible dicarboxylate building block, 4,4'-bipyridine and transition metal ions [Cd(II), Zn(II), and Mn(II)] as metal centers in DMF and aqueous media. These MOFs formulated as [Cd(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Cd-ADA-1), [Mn(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Mn-ADA-1), Zn(ADA)(4,4'-bipy)(0.5) (Zn-ADA-1), and [Mn(HADA)(2)(4,4'-bipy)(H(2)O)(2)] (Mn-ADA-2) (ADA = 1,3-adamantanediacetate, 4,4'-bipy = 4,4'-bipyridine and DMF = N,N'-dimethyl formamide) display interesting 1D, 2D and 3D structural features depending on the solvent of synthesis. All these MOFs were structurally determined by single-crystal X-ray diffraction. The coordination modes of this ligand are discussed and in addition, thermal stability and hydrogen (H(2)) and carbon-dioxide (CO(2)) adsorption properties of Cd-ADA-1, Mn-ADA-1 and Zn-ADA-1 are also presented. Hydrogen sorption at 77 K and up to 1 atm is found to be 0.42, 0.72 and 1.36 wt% without saturation for Zn-ADA-1, Mn-ADA-1 and Cd-ADA-1 samples.

Structural diversity in partially fluorinated metal organic frameworks (F-MOFs) composed of divalent transition metals, 1,10-phenanthroline, and fluorinated carboxylic acid - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Vanka, Kumar; Banerjee, Rahul (Crystal Growth & Design, 2010)
Seven new partially fluorinated metal-organic frameworks (F-MOFs) have been synthesized under different solvothermal conditions (H(2)O or N,N-dimethylformamide (DMF)) from transition metal cations [Zn(II), Co(II), and Mn(II)], 1,10-phenanthroline (phen), and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) to determine the influence of reaction conditions on the formation of metal-organic frameworks. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. Of the seven materials, two contain three-dimensional connectivity: Co(3)(hfbba)(6)(phen)(2) (F-MOF-6) and Mn(3)(hfbba)(6)(Phen)(2) (F-MOF-10). Three materials are one-dimensional structures: Zn(hfbba)(0.5)(phen)(HCO(2)) (F-MOF-8), Mn(Hhfbba)(2)(Phen) (F-MOF-11), and [Mn(hfbba)(2)(dm-phen)]center dot(H(2)O) (F-MOF-11A). Lastly, Co(hfbba)(phell)(2)center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-7) and Zn(hfbba)(phen)(2)center dot 2(H(2)hfbba) (H(2)O)-(HCO(2)) (F-MOF-9) are discrete zero-dimensional molecular complexes. F-MOF-6 and -10, which feature it three-dimensional (3D) framework with pcu topolgy are formed in DMF like F-MOF-8 and at 85 degrees C. The remaining F-MOFs are formed by a solvothermal reaction at 120 degrees C in water. F-MOF-7 and -9 are isostructural discrete zero-dimensional molecular complexes (a similar to 19.5; b similar to 13.7; c similar to 26.2/29.6 angstrom; beta similar to 99.9/120.04; V similar to 6840 angstrom(3)). All these F-MOFs were structurally determined by single-crystal X-ray diffraction. Solid-state properties such its UV-vis and the thermal stability of F-MOF-6 to -11A have also been studied. Insight into the factors influencing the preferred crystallization of a specific complex over others has been obtained from full quantum chemical (QM) calculations using density functional theory (DFT).

Synthesis and structural comparisons of five new fluorinated metal organic frameworks (F-MOFs) - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Banerjee, Rahul (Crystengcomm, 2010)
A series of fluorinated metal-organic frameworks (F-MOFs) have been successfully synthesized under hydrothermal condition using 4,40-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) as a flexible dicarboxylate building block, Cu(+2) and various heterocyclic co-ligands. These F-MOFs formulated as [Cu(hfbba)(phen)(2)]center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-1), [Cu(hfbba)(2)(2,2'-bipy) 2(H(2)O)] (F-MOF-2), [Cu(hfbba)(4,4'-dime-2,2'-bipy)(HCO(2))]center dot(hfbba)(H(2)O) (F-MOF-3), [Cu(2)(hfbba)(2)(3-mepy)(2)]center dot(DMF) 2(3-mepy) (F-MOF-4), and [Cu(hfbba)(2)(phen)(2)]center dot 0.5(DMF) (F-MOF5) (hfbba = 4,4'-(Hexafluoroisopropylidene) bis(benzoate), phen 1,1'-phenanthroline; 2,2'-bipy 2,2'-bipyridine; 4,4'dime-2,2'-bipy 4,4'-dimethyl 2,2'-bipyridine; 3-mepy 3-methyl-pyridine and DMF dimethyl formamide) display interesting H-bonded, 1D and 2D structural features. All these F-MOFs were structurally determined by single-crystal X-ray diffraction. F-MOF-1 and 5 form a distorted octahedral Cu(+2) secondary building unit (SBU). F-MOF-5 forms a one-dimensional architecture constructed from Cu(2+) ions bridged by phen anions and two types of 4 hfbba ligands while in F-MOF-1, two among the three acid co-ligands are not coordinated with Cu(2+) ions. F-MOF-2 displays dinuclear SBUs within the three-dimensional frameworks whereas F-MOF-3 displays mononuclear SBUs and forms a one-dimensional chain. F-MOF-4 display a interesting 2D framework with conventional Cu(2)(CO(2))(4) paddle wheel SBU. In the crystal structures four hfbba ligands, each coordinated to a dicopper paddlewheel unit via one of their carboxylate groups. Solid-state properties such as UV-vis and thermal stability of F-MOF-1-5 have also been studied.

Self-assembled one dimensional functionalized metal-organic nanotubes (MONTs) for proton conduction - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Two self-assembled isostructural functionalized metal-organic nanotubes have been synthesized using 5-triazole isophthalic acid (5-TIA) with In(III) and Cd(II). In-and Cd-5TIA possess one-dimensional (1D) nanotubular architecture and show proton conductivity along regular 1D channels, measured as 5.35 x 10(-5) and 3.61 x 10(-3) S cm(-1) respectively.

Solution mediated phase transformation (RHO to SOD) in porous Co-imidazolate based zeolitic frameworks with high water stability - Biswal, Bishnu P.; Panda, Tamas; Banerjee, Rahul (Chemical Communications, 2012)
Here we report a highly porous, water stable Co based ZIF [CoNIm (RHO)] and its solution mediated phase transformation to a less porous and water unstable ZIF [CoNIm (SOD)]. CoNIm (RHO) has high Langmuir surface area [2087 m(2) g(-1)] as well as high water adsorption [200 cm(3) (STP) g(-1)] capacity.

Structural isomerism leading to variable proton conductivity in indium(III) isophthalic acid based frameworks - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2013)
Proton conductivity has been studied thoroughly in two isomeric In(III)-isophthalate based MOFs. In-IA-2D-1 is capable of showing proton conductivity (3.4 x 10(-3) S cm(-1)) under humidified conditions (98% RH), whereas In-IA-2D-2 can conduct protons (2.6 x 10(-5) S cm(-1)) under humidified as well as anhydrous conditions.